Hospital‐physician integration and Medicare's site‐based outpatient payments. (27th January 2021) - Post, Brady; Norton, Edward C.; Hollenbeck, Brent; Buchmueller, Thomas; Ryan, Andrew M.
Abstract: Objective: To determine the relationship between Medicare's site‐based outpatient billing policy and hospital‐physician integration. Data sources: National Medicare claims data from 2010 to 2016. Study Design: For each physician‐year, we calculated the disparity between Medicare reimbursement under hospital ownership and under physician ownership. Using logistic regression analysis, we estimated the relationship between these payment differences and hospital‐physician integration, adjusting for region, market concentration, and time fixed effects. We measured integration status using claims data and legal tax names. Data Collection: The study included integrated and non‐integrated physicians who billed Medicare between January 1, 2010, and December 31, 2016 ( n  = 2 137 245 physician‐year observations). Principal Findings: Medicare reimbursement for physician services would have been $114 000 higher per physician per year if a physician were integrated compared to being non‐integrated. Primary care physicians faced a 78% increase, medical specialists 74%, and surgeons 224%. These payment differences exhibited a modest positive relationship to hospital‐physician vertical integration. An increase in this outpatient payment differential equivalent to moving from the 25th to 75th percentile was associated with a 0.20 percentage point increase in the probability of integrating with a hospital (95% CI: 0.0.10‐0.30). This effect was slightly larger among primary care physicians (0.27, 95% CI: 0.18 to 0.35) and medical specialists (0.26, 95% CI: 0.05 to 0.48), while not significantly different from zero among surgeons (−0.02; 95% CI: −0.27 to 0.22). Conclusions: The payment differences between outpatient settings were large and grew over time. Even routine annual outpatient payment updates from Medicare may prompt some hospital‐physician vertical integration, particularly among primary care physicians and medical specialists.